A Second New Choroidal Osteoma in the Same Eye: Differences between Them with New Imaging Techniques. (12th March 2015) - Sambricio, Javier; Fernández-Reyes, Marifé; De-Lucas-Viejo, Beatriz; Bengoa-González, Álvaro; Mencía-Gutiérrez, Enrique
Abstract : The authors introduce a 42-year-old woman with a choroidal osteoma. After 10 years the patient presented a second choroidal osteoma in the same eye; this osteoma has been growing in the last years. New tests that were unavailable during the first diagnosis were performed such as Fundus Autofluorescence or Enhanced Depth Imaging-Optical Coherence Tomography (EDI-OCT). These tests show characteristics of the tumors and allow us to realize a visual prognosis for the patient.